Effect of Polymer Concentration on the Structure and Performance of PEI Hollow Fiber Membrane Contactor for CO2 Stripping - Rosmawati, Naim; A. Fauzi, Ismail (Elsevier Ltd, 2013)
A series of polyetherimide (PEI) hollow fiber membranes with various polymer concentrations (13–16 wt.%) for CO2 stripping process in membrane contactor application was fabricated via wet phase inversion method. The PEI membranes were characterized in terms of liquid entry pressure, contact angle, gas permeation and morphology analysis. CO2 stripping performance was investigated via membrane contactor system in a stainless steel module with aqueous diethanolamine as liquid absorbent. The hollow fiber membranes showed decreasing patterns in gas permeation, contact angle, mean pore size and effective surface porosity with increasing polymer concentration. On the contrary, wetting pressure of PEI membranes has enhanced significantly with polymer concentration. Various polymer concentrations have different effects on the CO2 stripping flux in which membrane with 14 wt.% polymer concentration showed the highest stripping flux of 2.7 × 10−2 mol/m2 s. From the performance comparison with other commercial membrane, it is anticipated that the PEI membrane has a good prospect in CO2 stripping via membrane contactor.